Transepiphyseal Fracture‐Dislocation of the Hip inan Adolescent: A Rare Clinical Case - Moreira, Andreia G. (2024)
Hip fracture‐dislocations in children and adolescents are rare and severe injuries. Surgical treatment is urgent and, even with adequate and timely treatment, the complication rate is high. The most common complication is osteonecrosis of the femoral head and the main risk factors include fracture type and displacement. A 13‐year‐old boy presented after a high‐energy trauma, having sustained a fracture‐dislocation of the left hip, with complete separation of the proximal femoral epiphysis, incarcerated in a fracture of the acetabulum. He underwent surgery with open reduction of the femoral epiphysis and fixation with two Kirschener wires, hip joint reduction, open reduction of the acetabulum fracture and internal fixation with a reconstruction plate. The immediate postoperative evolution was favorable, but at 10 months radiological signs of osteonecrosis of the femoral head were already visible. Clinically, 5 years after the accident, he maintains good function, with a Non Arthritic Hip Score of 80/100. Pediatric hip fracture‐dislocation is a therapeutic challenge and has a poor prognosis. In addition to timely and appropriate treatment, it is essential to manage the expectations of patients and their families.